Current Trends in Augmented Reality to Improve Senior High School Students’ Skills in Education 4.0: A Systematic Literature Review - Yanti Febri; Lufri Lufri; Ahda Yuni (Open Education Studies)
Augmented reality (AR) became increasingly popular in education worldwide as a useful tool for improving student engagement, teamwork, and problem-solving abilities to enhance students’ skills in Education 4.0 (E4.0). This research aimed to analyze and highlight several research publications that examined the use of AR to improve the skills of senior high school students in E4.0. This research employed the systematic literature review method. Searching for relevant articles using the Publish or Perish application, identifying articles, filtering articles, selecting potential articles using the Preferred Reporting Items for Systematic Reviews (PRISMA) diagram, analyzing and synthesizing findings qualitatively, and preparing research reports. We obtained articles from three databases: Google Scholar, Web of Science, and Scopus. The research results indicated an increasing use of AR in E4.0 to enhance high school students’ skills, including creative thinking and innovation, critical thinking and problem-solving, communication, and collaboration.